Dental Implantology in the Treatment of the After-Effects of the Juvenile Paresis Nervus Facialis - P. Prachár; S. Bartáková; P. Černochová; J. Vaněk (Czech Dental Chamber, 2013)
Introduction and objective: In this paper, the authors deal with the problems of juvenile paresis n. facialis and after-effects of this disease. The authors divide the hypodontia acquired and hereditary. Of these, allocating hypodontia obtained on the basis of agents, which include paresis n. facialis. Further describe the genesis and characteristics of paresis n. facialis. They show link between disease and paralysis of the facial nerve. It also describes the development in the permanent dentition and dental damage fetuses. This damage corresponding time distribution in developing dentition. Methods: The authors show examples of diseases resulting from facial nerve palsy in seven years of age. It was a juvenile unilateral paresis. There were hypodontia true and , which were the result of damage at a given age. Outside the teeth issue here, the issue of mandible and soft tissues of the face. The patient was determined throughout the treatment plan with several dental skills. Results: It was first approached to extractions poor dentition, which was due to undeveloped embryos incapable of further dental prosthetic use. This was followed by augmentation of alveolar mainly in the horizontal dimension with partial vertical increase in bone height sept teeth covering the defect. Furthermore, the advertised dental implants in the lower jaw so prepared, together with implantation in the right hypodontia. Followed by addition of aesthetic soft tissue prosthesis. The patient was further evaluated using X-ray view from a distance for 10 years from the start of therapy. Conclusion: Paresisi n. facialis is a disease where the terms of dentistry causes very serious damage to the dental germs, with the age. Frequently there are augmentation techniques to supplement defective alveolar mainly in the horizontal direction, followed by treatment with dental implants. Subsequently defect of soft tissues of the face affected parties leads us to supplement the soft tissues of the mouth using prostheses. The authors thus emphasize the complexity of the treatment with respect to disability not only permanent dentition, but also the surrounding structures.